Ultrafine Co-Species Interspersed g-C3N4 Nanosheets and Graphene as an Efficient Polysulfide Barrier to Enable High Performance Li-S Batteries - Shanxing Wang; Xinye Liu; Yuanfu Deng (Molecules, 2023)
Lithium-sulfur (Li-S) batteries are regarded as one of the promising advanced energy storage systems due to their ultrahigh capacity and energy density. However, their practical applications are still hindered by the serious shuttle effect and sluggish reaction kinetics of soluble lithium polysulfides. Herein, g-C3N4 nanosheets and graphene decorated with an ultrafine Co-species nanodot heterostructure (Co@g-C3N4/G) as separator coatings were designed following a facile approach. Such an interlayer can not only enable effective polysulfide affinity through the physical barrier and chemical binding but also simultaneously have a catalytic effect on polysulfide conversion. Because of these superior merits, the Li-S cells assembled with Co@g-C3N4/G-PP separators matched with the S/KB composites (up to ~70 wt% sulfur in the final cathode) exhibit excellent rate capability and good cyclic stability. A high specific capacity of ~860 mAh g−1 at 2.0 C as well as a capacity-fading rate of only ~0.035% per cycle over 350 cycles at 0.5 C can be achieved. This bifunctional separator can even endow a Li-S cell at a low current density to exhibit excellent cycling capability, with a capacity retention rate of ~88.4% at 0.2 C over 250 cycles. Furthermore, a Li-S cell with a Co@g-C3N4/G-PP separator possesses a stable specific capacity of 785 mAh g−1 at 0.2 C after 150 cycles and a superior capacity retention rate of ~84.6% with a high sulfur loading of ~3.0 mg cm−2. This effective polysulfide-confined separator holds good promise for promoting the further development of high-energy-density Li-S batteries.